ISU PLURALISME DALAM AL-QUR’AN - Abdul Basir (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2021)
The discourse on religious pluralism is a very hotly discussed issue, especially among Muslims. This can be seen from the birth of books, works, writings in the mass media, congresses, seminars, discussions, and dialogues that discuss religious pluralism. The factors behind the emergence of this discourse, among others, are the conflicts that are rife between religious communities which often stem from excessive truth claims. This discourse aims to create harmony and peace between religious communities. The Qur'an itself recognizes the existence of other religions and calls on its people to live side by side and respect each other. Islam came as rahmatan lil'almin, but the reality that happened was not in sync with ideals. Then the question arises, where is Islam which is rahmatan lil'alamin located? In fact, here and there there are many Muslims who cannot deal with diversity wisely, as taught in the Qur'an. Then how is the guidance of the Qur'an to address differences? Based on that, this paper will discuss the guidance of the Qur'an in responding to religious pluralism with a descriptive-analytical method